The Role of Digital Leadership in Improving the Quality of Electronic Services: Case Study of the Land Office in Surakarta, Indonesia - Aulawi, Ikhlasul Akmal; Kutanegara, Pande Made; Ikhwan, Hakimul; Prianggara, Yoga (Populasi, 2025)
This study analyzes the process of electronic services at the Surakarta City Land Office and the role of digital leadership in improving service quality. The research used a descriptive qualitative method with data obtained through in-depth interviews with 18 informants, observations, and document studies. Data triangulation is carried out to ensure the validity of the information. The results of the study show that electronic services, such as electronic mortgage (HT-El), elimination of Mortgage Rights/electronic roya (Roya-El), and electronic land registration certificate (SKPT-El) increase efficiency, transparency, and accuracy in the management of land services. Digitization is carried out gradually through the conversion of physical documents into electronic documents with encryption technology for data security. The electronic dashboard integrated with the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) allows for direct supervision, increasing accountability and accelerating services. The success of digitalization depends heavily on visionary digital leadership. The Head of Office not only acts as a decision-maker, but also as a driver of change, motivates employees, and builds external collaboration. This leadership creates a strong digital culture, strengthens relationships with stakeholders, and encourages a change in digital mindset. Innovations such as electronic certificates, Certificate Printing Platform, and the “Sentuh Tanahku” application improve the quality of electronic-based services, especially in the E-S-Qual and E-Recs-Qual dimensions, providing an efficient, transparent, and responsive experience for users.